HUBUNGAN PERSEPSI ATAS KUALITAS INFORMASI KEUANGAN DESA, PARTISIPASI MASYARAKAT, DAN TRANSPARANSI PENGELOLAAN DANA DESA DENGAN PERSEPSI KESEJAHTERAAN MASYARAKAT DESA TEMA TANA - Alvindo Bani Pangga Leghu (ITB AAS Indonesia Surakarta, 2026)
This study examines the associations of perceived village financial information quality, community participation, and transparency in Village Fund management with perceived community welfare in Tema Tana Village, West Sumba. A cross-sectional survey was conducted using purposive sampling. Of 86 questionnaires distributed, 79 valid responses were analyzed using multiple linear regression. Perceived village financial information quality was not significantly associated with perceived community welfare (B = 0.014; β = 0.018; p = 0.833). In contrast, community participation (B = 0.356; β = 0.441; p < 0.001) and transparency in Village Fund management (B = 0.437; β = 0.485; p < 0.001) showed positive and significant associations. The overall model was significant, F(3, 75) = 87.412, p < 0.001, with an adjusted R² of 0.769. These findings indicate that perceived welfare is more closely associated with community involvement and transparency than with the perceived technical quality of financial information. Because the study used cross-sectional data from one village, the results should not be interpreted causally or generalized beyond comparable settings.